ANALISIS TUGAS POKOK DAN FUNGSI PEMBIMBINGAN TERHADAP KLIEN PEMASYARAKATAN DI BAPAS KELAS I PALEMBANG - Chandra, Adhe; Sudirman, Sudirman; Nata K, Yandra; Irawan, Surya (Journal Evidence Of Law, 2022)
Guidance is a series of law enforcement in the community which is carried out through efforts to restore the unity of life, life and livelihood of correctional clients so that they can realize their mistakes, improve themselves and not repeat criminal acts and can be accepted again by the community environment. Guidance to correctional clients is carried out by improving the quality, devotion to God Almighty, intellectual, attitudes and behaviors, professional, physical and spiritual health of correctional clients. However, this mentoring process has not been implemented optimally, resulting in re-violations of the law committed by correctional clients. That is what prompted the author to compile this scientific paper with the title Analysis of the Implementation of Correctional Client Guidance at Balai Pemasyarakatan Kelas I Palembang. This study has a formulation of problems in the form of: How is the correctional client guidance system at Balai Pemasyarakatan Kelas I Palembang?, as well as the inhibiting and supporting factors that affect the implementation of the correctional client guidance system at Balai Pemasyarakatan Kelas I Palembang?. Furthermore, this study aims to describe and explain the system of guiding correctional clients at Balai Pemasyarakatan Kelas I Palembang, as well as describe and analyze the factors that affect the correctional client guidance system at Balai Pemasyarakatan Kelas I Palembang.